The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.20897/ejosdr/85933
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Treatment of Textile Wastewater by Aquatic Plants (Macrophytes) and Algae

Abstract: Textile wastewater contains large quantities of organic and inorganic compounds, which cause toxic and hazardous pollutants in the environment. Efficacy, efficiency and feasibility of the biological treatment method using macrophytes and algae were investigated, and various physicochemical parameters (TSS, TDS, pH, color, EC, DO, BOD, COD and metal concentration) were also analyzed. In pre-treated sample, TSS, TDS, pH, temperature, DO, BOD, COD, EC and color were recorded as 913 mg/L, 2250 mg/L, 9.4, 41°C, 2.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The high value of electrical conductivity value of 7260 µS/cm was due to the use of high quantities of salts for dyeing fixing, such as sodium chloride, sodium carbonate, sodium bicarbonate and sodium hydroxide (Correia et al, 1994;Rodrigues et al, 2013;Khatri et al, 2015). Although indispensable for the living organisms, the excess of salts was seen to decrease the osmotic potential of the soil, decline the water absorption of seeds and cause inhibitory effect in plants (Flowers et al, 2014;Geilfus et al, 2018;Roy et al, 2018). Studies also indicated that the excess of salts was responsible to suppress the seed germination, inhibit the root growth and cause significant effects on the development of plants (Foy, 1992;Joutti et al, 2003).…”
Section: Physicochemical Parametersmentioning
confidence: 99%
“…The high value of electrical conductivity value of 7260 µS/cm was due to the use of high quantities of salts for dyeing fixing, such as sodium chloride, sodium carbonate, sodium bicarbonate and sodium hydroxide (Correia et al, 1994;Rodrigues et al, 2013;Khatri et al, 2015). Although indispensable for the living organisms, the excess of salts was seen to decrease the osmotic potential of the soil, decline the water absorption of seeds and cause inhibitory effect in plants (Flowers et al, 2014;Geilfus et al, 2018;Roy et al, 2018). Studies also indicated that the excess of salts was responsible to suppress the seed germination, inhibit the root growth and cause significant effects on the development of plants (Foy, 1992;Joutti et al, 2003).…”
Section: Physicochemical Parametersmentioning
confidence: 99%